Measurement of band gap energy of ZnO doped with TiO2, Bi2O3 and Co3O4 by photopyroelectric technique - Cheong, Pui Teng. (2008., 2008)
This study is mainly focused on the measurement of band gap energy of 98.6mol% of ZnO doped with 0.5 mol% of TiO2, 0.5 mol% of BiO3 and 0.4 mol% of Co3O4 by using the photopyroelectric technique. The samples prepared were sintered at five different sintering temperatures which are 1180, 1210, 1240, 1270 and 1300 °C. The sintering time for this study is 30 and 90 minutes. A polyvinylidene difluoride film was used as a detector and the wavelength of incident light was scanned in the range of 300 to 800 nm. The light beam was mechanically chopped at 9 Hz of frequency. The thin layer of samples that deposited on 17 um thick stainless steel foil were exposed to incident radiation. The data of PPE amplitude signal obtained was used to determine the band gap energy of samples. The increase in grain sizes and decrease in density of sample with sintering temperature also investigated in this study. The development of pores in sample causes the decrease in density. As a conclusion, the band gap energy obtained through the experiment is lowered than that of pure ZnO. This is due to the doping process has created intermediate energy level in the band gap.
Project paper (B.S. (Hons.)) - Universiti Putra Malaysia, 2008.